Scalable parallel ultrafast optical random bit generation based on a single chaotic microcomb - Pu Li; Qizhi Li; Wenye Tang; Weiqiang Wang; Wenfu Zhang; Brent E. Little; Sai Tek Chu; K. Alan Shore; Yuwen Qin; Yuncai Wang (Light: Science & Applications, 2024)
Abstract Random bit generators are critical for information security, cryptography, stochastic modeling, and simulations. Speed and scalability are key challenges faced by current physical random bit generation. Herein, we propose a massively parallel scheme for ultrafast random bit generation towards rates of order 100 terabit per second based on a single micro-ring resonator. A modulation-instability-driven chaotic comb in a micro-ring resonator enables the simultaneous generation of hundreds of independent and unbiased random bit streams. A proof-of-concept experiment demonstrates that using our method, random bit streams beyond 2 terabit per second can be successfully generated with only 7 comb lines. This bit rate can be easily enhanced by further increasing the number of comb lines used. Our approach provides a chip-scale solution to random bit generation for secure communication and high-performance computation, and offers superhigh speed and large scalability.